JUAL BELI BARANG DENGAN CARA IFSAD DI KELURAHAN WEK-I KECAMATAN PADANGSIDIMPUAN UTARA - Elisa Rizky Siregar; Zul Anwar Ajim Harahap (Tazkir : Jurnal Penelitian Ilmu-ilmu Sosial dan Keislaman, 2018)
The problem in this research is how the practice of buying and selling goods by means of IFSAD Wek-I Subdistrict Padangsidimpuan North District, and how Fiqh Muamalah reviews about buying and selling goods by Ifsad in Wek-I Subdistrict, Padangsidimpuan Utara District. The purpose of this study was to find out the practice of buying and selling goods by means of Ifsad Wek-I Subdistrict, Padangsidimpuan North District, and to find out about Fiqh Muamalah review about the sale and purchase of goods by Ifsad in Wek-I Subdistrict, Padangsidimpuan Utara District. This type of research is qualitative research, namely the research process to produce data in the form of explanations, both written and unwritten with the people studied. The researchers examined were 16 sellers and 7 buyers. The results of this study obtained ifsad sale and purchase of goods carried out by some traders in Wek-I Sub-District, North Padangsidimpuan District, namely if the traders sell by weighing and wrapping the cooking oil and granulated sugar with each plastic-sized benchmark. Like wrapping each cooking oil in a plastic measuring ¼ kg. When the buyer comes the seller immediately gives the goods that have been wrapped in advance without any weighing in front of the buyer so as to raise doubts about the buyer. Each package is usually not in accordance with the scales, if the buyer returns to the item purchased because the scale is less, the seller does not want to give less than the purchased, because the seller says that the scales are sold accordingly, while the stall is not indicated when the buyer arrives. An Overview of Muamalah Fiqh on the sale and purchase by Ifsad in Wek-I Subdistrict, Padangsidimpuan Utara Subdistrict has not been in accordance with the provisions contained in one of the conditions of the sale and purchase contract that is known to be known, the amount, the size, or the other sizes.